"If one is Orthodox, one should not strive for luxury": political values and the changing strategies of anti-corruption CSOs in Russia. Issue 8 (17th November 2022) - Chiarvesio, Francesca; Di Puppo, Lili
ABSTRACT: By analysing the changing strategies adopted by anti-corruption CSOs in Russia, this article sheds light on the role of political values in the anti-corruption field. We argue that the rise of a conservative discourse in Russia that places greater emphasis on values has created both limitations and opportunities for CSOs. With this 'conservative turn', the question of 'foreign influence' has gained prominence in political debates. As an effect of this discourse, the label 'foreign' has been applied to certain CSOs, limiting their ability to claim neutrality on the basis of expert knowledge. In the context of the fight against corruption, however, references to the 'foreign' are present both in the government's rhetoric and in societal narratives. By responding to a conservative anti-corruption discourse 'from below', certain CSOs have adopted a new strategy of reaching out to an ideologically diverse audience to maintain their non-political positioning.